Solid-state NMR insights into alcohol adsorption by metal–organic frameworks: adsorption state, selectivity, and adsorption-induced phase transitions. Issue 28 (18th March 2022) - Khan, Arafat Hossain; Salout, Sara Amanzadeh; Shupletsov, Leonid; De, Ankita; Senkovska, Irena; Kaskel, Stefan; Brunner, Eike
Abstract : Alcohol adsorption by metal–organic frameworks (ZIF-8 and ZIF-11) in aqueous solutions is investigated including alcohol mixtures. Abstract : Alcohol adsorption by metal–organic frameworks (ZIF-8 and ZIF-11) in aqueous solutions is investigated including alcohol mixtures. Solid-state 13 C NMR spectroscopy is demonstrated to be well-suited for such liquid-phase adsorption studies at the molecular level. Adsorption-induced immobilization could be visualized. Finally, an unexpected phase transition of ZIF-11 was discovered.